2016
DOI: 10.1371/journal.pone.0159188
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recognition of Element Classes and Boundaries in the Birdsong with Variable Sequences

Abstract: Researches on sequential vocalization often require analysis of vocalizations in long continuous sounds. In such studies as developmental ones or studies across generations in which days or months of vocalizations must be analyzed, methods for automatic recognition would be strongly desired. Although methods for automatic speech recognition for application purposes have been intensively studied, blindly applying them for biological purposes may not be an optimal solution. This is because, unlike human speech r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…if one bird sang more syllables per bout than another). Measuring the syllable error rate confirmed that TweetyNet consistently achieved similar error rates across the ten birds, as shown in Fig 4B. Because this metric was also used in [38] (as "note error rate"), we can compare our results directly to theirs. As indicated by blue circles in Fig 4B, the best-performing models in that study achieved syllable error rates of 0.83 and 0.46 with two and eight minutes of training data, respectively.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…if one bird sang more syllables per bout than another). Measuring the syllable error rate confirmed that TweetyNet consistently achieved similar error rates across the ten birds, as shown in Fig 4B. Because this metric was also used in [38] (as "note error rate"), we can compare our results directly to theirs. As indicated by blue circles in Fig 4B, the best-performing models in that study achieved syllable error rates of 0.83 and 0.46 with two and eight minutes of training data, respectively.…”
Section: Resultssupporting
confidence: 54%
“…We first set out to test whether our network robustly annotates syllables across a large number of individual birds. To do so, we made use of the publicly available repository of Bengalese Finch song [39], used to benchmark hybrid neural network-HMM models from [38] as referenced in Proposed Method and Related Work. The repository contains song from 10 individual birds, with hundreds of bouts of hand-annotated song for each bird.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations